Natural variations in TT8 and its neighboring STK confer yellow seed with elevated oil content in Brassica juncea - Lunwen Qian; Liu Yang; Xianjun Liu; Tianyi Wang; Lei Kang; Hao Chen; Yin Lu; Yukun Zhang; Shujie Yang; Liang You; Min Yao; Xingru Xiang; et al. (Proceedings of the National Academy of Sciences, 2025)
Seed color is a critical quality trait in numerous plant species. In oilseed Brassica crops, including rapeseed and mustard, yellow seeds are distinguished by their significantly higher oil content and faster germination rates compared to black or brown counterparts. Despite the agronomic significance of the yellow seeds being a prime breeding target, the mechanisms underlying elevated oil content remain obscure. In this study, we assembled the first telomere-to-telomere (T2T) genome of B. juncea and further investigated the genetic regulation, molecular mechanism, and the evolutionary history of yellow seeds in B. juncea. Through an analysis of allelic variation in the TRANSPARENT TESTA 8 ( TT8 ) genes across 1,002 worldwide B . juncea accessions, we traced the single origin of yellow seeds to approximately 2,300 y ago in Southwestern China. Furthermore, we discovered the MADS-box gene SEEDSTICK ( STK ) coevolved with TT8 , and they coordinately regulated seed size, oil accumulation, and seed coat proportion in B. juncea . These findings open broad avenues for targeted breeding of yellow-seeded Brassica crops with elevated oil content.